2020
DOI: 10.12998/wjcc.v8.i19.4349
|View full text |Cite
|
Sign up to set email alerts
|

Managing acute appendicitis during the COVID-19 pandemic in Jiaxing, China

Abstract: BACKGROUND Coronavirus disease 19 (COVID-19) is a global pandemic and has had a profound impact on our routine surgical activities. Acute appendicitis is the most common abdominal emergency worldwide. Therefore, it is highly essential to assess the influence the pandemic has on acute appendicitis. AIM To assess the efficacy of the management of acute appendicitis during the COVID-19 pandemic. METHODS We retrospectively analyzed 90 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
3
24
2
Order By: Relevance
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This systematic review included 14 studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] published in 2020. Five studies were based in the UK, three in USA, two in China, and one in Ireland, Nepal, Israel, and India.…”
Section: Study and Patients' Characteristicsmentioning
confidence: 99%
“…Some recent publications have claimed that the number of complicated appendicitis cases has increased in adults during the pandemic (8,10,11). However, there are few publications about children.…”
Section: Resultsmentioning
confidence: 99%